2013
DOI: 10.2478/nsad-2013-0030
|View full text |Cite
|
Sign up to set email alerts
|

Mothers Who abuse Alcohol and Drugs: Health and Social Harms among Substance-Abusing Mothers of Small Children in three Child Cohorts

Abstract: AIMS – The study looks at the prevalence and register-based indicators of substance abuse-related harms among mothers of small children. We examined the living conditions, various health and social harms and the differences between the users of different kinds of substances (alcohol only vs. drugs only vs. alcohol and other drugs). DATA & METHODS – Population-level register data was collected of all biological mothers of three Finnish birth cohorts (1991, 1997, 2002) describing the women's social problems, hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…The entries were specified according to type of substance abuse. The time frame covered also the four years prior to the child's birth, as substance abuse problems may have emerged before pregnancy [20]. Of all mothers who had children born in 2002, 2.0% ( n = 1062) had substance abuse problems according to the register data.…”
Section: Methodsmentioning
confidence: 99%
“…The entries were specified according to type of substance abuse. The time frame covered also the four years prior to the child's birth, as substance abuse problems may have emerged before pregnancy [20]. Of all mothers who had children born in 2002, 2.0% ( n = 1062) had substance abuse problems according to the register data.…”
Section: Methodsmentioning
confidence: 99%
“…A substantial literature in high-income countries has found that adult drinking is often implicated in child maltreatment, with proportions attributable to alcohol ranging upward from 16% (Laslett et al, 2013(Laslett et al, , 2015Single et al, 2000). Parental and carer alcohol misuse has been linked to a range of negative child outcomes, including poor role modelling and subsequent next-generation problematic drinking (Wilks et al, 1989;Yu, 2003), inability to maintain family routines (Gruenert et al, 2004;Velleman & Templeton, 2007), increased incidence of injuries and childhood diseases (Holmila et al, 2013), and child abuse and neglect (Laslett et al, 2012b(Laslett et al, , 2013. This article reports on and compares indicators of harm to children from adults' drinking in eight countries: Australia, Ireland, Chile, Sri Lanka, Thailand, Vietnam, Lao People's Democratic Republic (PDR), and Nigeria.…”
mentioning
confidence: 99%
“…Thereafter the women were categorised according to type of substance abuse. Because very few women had alcohol as their only preferred drug (6%) it was not feasible to distinguish between alcohol abuse, mixed alcohol and drug abuse, and drug abuse (Holmila et al, 2013). Therefore, women who had alcohol as one of their drugs of choice (32%) were placed in one group (AD), and those whose drugs of choice did not include alcohol (68%) in another (DD).…”
Section: Methodsmentioning
confidence: 99%
“…Nonetheless, epidemiological and clinical studies on the foetal impact of alcohol, drug, and tobacco use during pregnancy are plentiful. These studies usually focus on outcomes such as birth weight, birth deficiencies, as well as long-term effects on the child's health, social and psychological development (Bauer et al, 2011;Della Grotta et al, 2010;Higgins, Clough, & Wallerstedt, 1995;Hjerkinn, Rosvold, & Lindbaek, 2009;Holmila, Raitasalo, & Kosola, 2013;Kissin, Svikis, Morgan, & Haug, 2001;Moe, 2002;Shankaran et al, 2007;Walton-Moss, McIntosh, Conrad, & Kiefer, 2009). Smaller clinical samples and register-based population studies have also been used to study substance abuse in connection with pregnancy or among mothers of small children (Holmila et al, 2013;Kahila, Gissler, Sarkola, Autti-Ramo, & Halmesmaki, 2010;Raitasalo, Holmila, Autti-Ramo, Martikainen, et al, 2015;Raitasalo, Holmila, Autti-Ramo, Notkola, & Tapanainen, 2015;Sarkola, Gissler, Kahila, Autti-Ramo, & Halmesmaki, 2012).…”
Section: Introductionmentioning
confidence: 99%